Second workshop on enactive approaches to mind in health and disease. (June 2019) - Fiebich, Anika
From 22 January 2019 to 24 January 2019, the 4E Cognition Group held the "Second Workshop on Enactive Approaches to Mind in Health and Disease" at Instituto de Investigaciones en Matemáticas Aplicadas y en Sistemas (IIMAS) in Mexico City, Mexico. The aim of the workshop was to discuss different kinds of mental impairments from an enactive stance, potentially contrasted with the basis of healthy mental processes and with other views of cognition.